USULAN PERANCANGAN TROLI Sebagai ALAT ANGKUT GALON Dengan PENDEKATAN ERGONOMI - Reynaldo Rizky Andreas Marpaung (2020)
Gallon hauling activities at the UPN Veteran Jakarta Faculty of Engineering from floor to fllor are still carried out without working tools. In the process workers still show abnormal work postures and can cuase operator to have Muscoloskeletal Disorder (MSD)s. The aim of this study is to provide a gallon aid consisting of an appropriate analysis and posture operator to eliminate Muscoloskeletel Disorder (MSD)s complaints. The method use are the Nordic Body Map (NBM), Rappid Upper Limb Assesment (RULA), Low Back Analysis (LBA), Ovako Working Analysis System (OWAS), Posture Evaluation Index (PEI). To get the PEI value issued using the siemens jack software. By involving these methods, the author will make a transportation is not carried out without working tools. From the result of the analysis the results obtained PEI value before the design of tool in posture 1 is 1,85 and after receiving a tool that is 0,96 and the result of PEI value before accessing the tool in posture 2 is 2,66.When after using the tool, the value of PEI becomes 1,24. The smaller the PEI value, the more ergonomic the worker's posture.